2022
DOI: 10.1021/jacs.1c12889
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Control of Exciton Dynamics in Bioinspired Cofacial Porphyrin Dimers

Abstract: Understanding how the complex interplay among excitonic interactions, vibronic couplings, and reorganization energy determines coherence-enabled transport mechanisms is a grand challenge with both foundational implications and potential payoffs for energy science. We use a combined experimental and theoretical approach to show how a modest change in structure may be used to modify the exciton delocalization, tune electronic and vibrational coherences, and alter the mechanism of exciton transfer in covalently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…To design more efficient OPV materials, we need to have an accurate description of the mechanisms for the photoinduced nonadiabatic dynamics. Incredible efforts have been made in recent decades to elucidate the molecular underpinnings of such phenomena using both experimental and theoretical techniques. For example, two-dimensional electronic spectroscopy provides rich knowledge on ultrafast dynamical information of CT and EET in realistic light-harvesting molecules in complex or condensed-phase systems. Theoretical description of nonadiabatic dynamics has advanced significantly. Mixed quantum–classical dynamics such as mean-field Ehrenfest , and fewest-switches surface hopping (FSSH) , are the most popular approaches for simulating the nonadiabatic dynamics in molecular or extended nanoscale systems (up to hundreds of atoms) with the help of on-the-fly electronic structure calculations and the recent machine-learning-based acceleration. …”
Section: Introductionmentioning
confidence: 99%
“…To design more efficient OPV materials, we need to have an accurate description of the mechanisms for the photoinduced nonadiabatic dynamics. Incredible efforts have been made in recent decades to elucidate the molecular underpinnings of such phenomena using both experimental and theoretical techniques. For example, two-dimensional electronic spectroscopy provides rich knowledge on ultrafast dynamical information of CT and EET in realistic light-harvesting molecules in complex or condensed-phase systems. Theoretical description of nonadiabatic dynamics has advanced significantly. Mixed quantum–classical dynamics such as mean-field Ehrenfest , and fewest-switches surface hopping (FSSH) , are the most popular approaches for simulating the nonadiabatic dynamics in molecular or extended nanoscale systems (up to hundreds of atoms) with the help of on-the-fly electronic structure calculations and the recent machine-learning-based acceleration. …”
Section: Introductionmentioning
confidence: 99%
“…As for the temperature, we assume that it is uniform throughout the structure and identical for all degrees of freedom, nuclear and electronic. We focus in this study on charge current only, but control of exciton dynamics and realizing longrange exciton energy currents are similarly of an interest, and they display rich coherent-incoherent effects [57][58][59] .…”
Section: Conventional Mechanisms and Open Questions A Setup And Conve...mentioning
confidence: 99%
“…There is a growing number of reports of multichromophore arrays that have explored different modes of TS electronic interactions, TB interactions via π-networks or σ-bonds, or combined TS and TB interactions. Such interchromophore electronic coupling has been exploited to afford fluorophores with enhanced properties, , including for use in singlet fission. ,,,, It is normally assumed that TB and TS interactions complement each other in an additive manner. However, a recent report demonstrated that TB and TS interactions between two covalently linked porphyrins in a slipped cofacial arrangement destructively interfere, resulting in an increase in the calculated electronic coupling when the linker is removed …”
Section: Introductionmentioning
confidence: 99%
“…Examples of other porphyrinic systems include dyads with directly linked units , or systems that have cofacial, slipped cofacial, , or edge-to-edge arrangements that employ ethynyl or butadienyl linkers . Synthetic arrays have been prepared in which hydroporphyrins (chlorins or bacteriochlorins) are directly attached , or held in a cofacial arrangement via various linkers. A few examples of dyads from our prior studies that involve the joining of two chlorins or two bacteriochlorins via a vinylene (i.e., 1,2-ethenediyl), ethynyl, or butadiynyl linker are shown in Chart . Also shown is the dyad denoted trans- C1 in which two chlorins are joined via a linker comprised of a 3,4-dimethoxycarbonyl-hexa-3-en-1,5-diyne linker that contains a triple–double–triple-bond (enediyne) motif .…”
Section: Introductionmentioning
confidence: 99%